Does Musharakah Mutanaqisah converge with Bai Bithamin Ajil and conventional loans?. Issue 5 (11th September 2017) - Kashi, Aghilasse; Mohamad, Azhar
Abstract : Purpose: This study aims to examine the disputable Shari'ah and the technical issues underlying the implementation of the Musharakah Mutanaqisah partnership (MMP) model in home financing by Islamic banks in Malaysia. It assesses whether this much-lauded facility is in line with Shari'ah rules and whether it diverges from or converges to the Bay' Bithaman Ajil (BBA) and conventional loan models. Design/methodology/approach: This study uses a qualitative methodology based on in-depth interviews to achieve these objectives. Findings: With regard to the issue of convergence, it is obvious from the interviewees' perceptions that the MMP model is converging with the BBA and conventional housing loans. Originality/value: Many factors were mentioned as the reasons for this convergence, with the most important being that Islamic banks are not operating in a fully fledged Islamic financial system, reducing the risk weightage and regulatory restrictions. As for Shari'ah compliance, controversy may result from the enhanced features that structure this facility. Though these enhanced features are Shari'ah compliant, it transforms the MMP model into a debt rather than a partnership contract.